CARBONIFEROUS CORALS AND CHAETETIDS FROM EXOTIC LIMESTONE BLOCK OF THE CRIMEA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
A chaetetid sponge and coral fauna from a Carboniferous exotic limestone block in the Lower Jurassic Esciorda olistostrome on the Bodrak River (Crimean Mountains) are described for the first time. The Bodrak exotic block is composed of massive limestone. It contains the chaetetid Chaetetes (Boswellia) sp., the tabulate coral Multithecopora sp., and poorly preserved rugose corals, including Dibunophyllum? sp., Cordibia? sp. and gen. et sp. indet. Only the fasciculate colonies of the rugose coral Lytvophyllum askynensis (Kossovaya, 2009) are confidently identified. The studied association of fossils is similar to that of the Donets Basin and the Urals and confirms the Lower Bashkirian age of the Bodrak limestone block.
Keywords: Carboniferous; Crimea; exotic block; Tabulate corals; Rugose corals; Chaetetid sponge